2014
DOI: 10.1111/imm.12339
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐4 up‐regulation of epidermal interleukin‐19 expression in keratinocytes involves the binding of signal transducer and activator of transcription 6 (Stat6) to the imperfect Stat6 sites

Abstract: Summary Interleukin‐19 (IL‐19) plays an important role in asthma by stimulating T helper type 2 (Th2) cytokine production. Interestingly, IL‐4, a key Th2 cytokine, in turn up‐regulates IL‐19 expression in bronchial epithelial cells, so forming a positive feedback loop. In atopic dermatitis (AD), another Th2 disease closely related to asthma, IL‐19 is up‐regulated in the skin. We propose to use IL‐4 transgenic (Tg) mice and human keratinocyte culture to delineate the molecular mechanisms involved in the up‐regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 49 publications
2
19
2
Order By: Relevance
“…Stimulation with IL-13, IL-22, or IFN-γ did not change IL-19 mRNA expression (data not shown). Thus, IL-19 mRNA expression by human keratinocytes increased by IL-17A or IL-4 stimulation, which was consistent with previous reports (4,5,7,8).…”
Section: Il-19 Expression Was Increased In Nhek By Il-17a or Il-4 Stisupporting
confidence: 93%
See 2 more Smart Citations
“…Stimulation with IL-13, IL-22, or IFN-γ did not change IL-19 mRNA expression (data not shown). Thus, IL-19 mRNA expression by human keratinocytes increased by IL-17A or IL-4 stimulation, which was consistent with previous reports (4,5,7,8).…”
Section: Il-19 Expression Was Increased In Nhek By Il-17a or Il-4 Stisupporting
confidence: 93%
“…Important cellular sources of IL-19 are thought to be monocytes (1)(2)(3), keratinocytes (4)(5)(6)(7)(8) and bronchial epithelial cells (9). IL-4 and IL-17A have been reported to induce IL-19 expression by human keratinocytes (4,5,7,8). The IL-19 receptor consists of IL-20R1 and IL-20R2 (10)(11)(12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…34 We have shown that IL-4 regulates hundreds of genes in keratinocytes. 12,13,15,16 IL-4-activated Stat6 binds to the GAS site to regulate its target genes, 15,16 and a typical GAS site for Stat6 consists of two palindromic half sites TTC and GAA with four spacing nucleotides in between. 15 Probably because of a lack of typical Stat6 binding sites, Stat6 has never been reported to bind to the loricrin promoter.…”
Section: Discussionmentioning
confidence: 99%
“…35 Since p300/CBP is the common coactivator for both loricrin and Stat6 target genes (e.g. CCL26 and IL-19 15,16 ), IL-4 signaling in keratinocytes may lead to activated Stat6 recruiting p300/CBP, thus sequestering this coactivator from the loricrin general transcription machinery (Figure 1). IL-4 has been shown to signal through different pathways, such as Jak/Stat, NF-kB, MAPK and PI3.…”
Section: Discussionmentioning
confidence: 99%